2023
DOI: 10.1002/puh2.56
|View full text |Cite
|
Sign up to set email alerts
|

A woman's lifetime risk disparities in maternal mortality in Ethiopia

Abstract: Background In Ethiopia, a woman's lifetime risk (chance) of dying from maternal causes over a woman's reproductive lifespan continues to be a public health challenge. However, detailed evidence is scarce. This study aimed to assess woman's lifetime risk disparities in maternal mortality. Methods National data from the Ethiopian Demographic and Health Survey from 2000 to 2016 were used. To determine a woman's lifetime risk of dying, first, the maternal mortality ratio was calculated. Then, a woman's lifetime ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is not just that Ethiopia is home to one of the highest burdens of maternal mortality globally 10 —roughly 4% of all maternal deaths—but that there is also large within-country variation to the disadvantage of underserved populations. 11 Literature showed that the lifetime risk of maternal death dropped from 4.6% in 2000 to 1.9% in 2016 in Ethiopia, 11 reflecting a ‘maternal mortality transition’ over time. However, theory-driven equity studies are needed on maternal health care services to inform the development of targeted interventions for underserved populations, thereby reducing gaps in maternal mortality to the point of no concern.…”
Section: Introductionmentioning
confidence: 99%
“…It is not just that Ethiopia is home to one of the highest burdens of maternal mortality globally 10 —roughly 4% of all maternal deaths—but that there is also large within-country variation to the disadvantage of underserved populations. 11 Literature showed that the lifetime risk of maternal death dropped from 4.6% in 2000 to 1.9% in 2016 in Ethiopia, 11 reflecting a ‘maternal mortality transition’ over time. However, theory-driven equity studies are needed on maternal health care services to inform the development of targeted interventions for underserved populations, thereby reducing gaps in maternal mortality to the point of no concern.…”
Section: Introductionmentioning
confidence: 99%